2018
DOI: 10.5380/rber.v7i2.58298
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Analysis of a Single-Phase Passive Cooling System

Abstract: The Fukushima Daiichi Accident highlighted the need for new sustainable technologies with high reliability for removing thermal load, in the thermal power area, with focus on nuclear power plants. This technology is designed for heat transfer from a hot source to a cold source by natural convection, without the need of active components, such as pumps or ventilators, reducing costs and improving reliability. In order to analyze the system parameters of such passive systems, with focus on its thermo-hydraulic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…The main observation in the experiments was thermal behavior at several zones in the NCL that was detected by K‐type thermocouples. Research conducted in papers 37,38 showed that the natural circulation loop reached a stable condition in less than 35 minutes. Therefore, the experiments were carried out for 60 minutes in each natural circulation loop configuration.…”
Section: Resultsmentioning
confidence: 99%
“…The main observation in the experiments was thermal behavior at several zones in the NCL that was detected by K‐type thermocouples. Research conducted in papers 37,38 showed that the natural circulation loop reached a stable condition in less than 35 minutes. Therefore, the experiments were carried out for 60 minutes in each natural circulation loop configuration.…”
Section: Resultsmentioning
confidence: 99%